Public expenditures on education and health in the Kyrgyz Republic before and during the global financial crisis - Roman Mogilevsky (Center for Social and Economic Research (CASE), 2011)
This paper analyses the public finance performance and the dynamics of government expenditures on education and health in the Kyrgyz Republic in 2007-2010, when the country was hit by the global economic crisis and then by an internal political crisis in 2010. Despite these crisis conditions, public health expenditures have increased substantially. In education, recurrent expenditures have been protected, while capital investments have been cut dramatically. Both sectors suffer from chronic under-financing, which results in an insufficient quality of services. The country's fiscal situation in the medium-term is going to be difficult, so efficiency-oriented reforms need to be implemented in health care and especially in education in order to sustain the development of these critical services in Kyrgyzstan.
Keywords: E62; H50; H51; H52; I18; I22; 330; Fiscal policy; Kyrgyzstan; Education financing; Health financing; Global economic crisis; Öffentliche Finanzen; Finanzpolitik; Bildungswesen; Bildungsfinanzierung; Bildungspolitik; Gesundheitswesen; Gesundheitskosten; Gesundheitsreform; Finanzkrise; Kirgisistan